Central corneal thickness and intraocular pressure in children with type 1 diabetes mellitus - Mohmad, Zulhisham (2023)
Purpose The aim of this study is to determine the mean central corneal thickness (CCT) and mean intraocular pressure (IOP) in children with type 1 diabetes mellitus (T1DM) and to determine the relationship between CCT and IOP on the one hand and age, gender, retinopathy hemoglobin A1c (HbA1c), and duration of diabetes on the other. Methods This is a case–control, hospital-based study conducted at Hospital Universiti Sains Malaysia between January 2022 and November 2022. Thirty-eight children with T1DM were recruited as cases, and 38 healthy children were recruited as controls. The cases and controls then underwent ophthalmic examination, IOP measurement, and CCT measurement using optical coherence tomography (OCT) of the right eye. Results The CCT and IOP values were higher in the T1DM group than in the control group, and the difference was statistically significant. The mean CCT was 542.18 ± 20.40 μm in the T1DM group, and 529.52 ± 26.17 μm in the control group (p-value <0.05). The mean IOP was 14.74 ± 2.05 mmHg in the T1DM group, and 13.68 ± 1.76 mmHg in the control group (p-value <0.05). The mean HbA1c was 10.68 ± 2.49% in the T1DM group. There was no diabetic retinopathy found in T1DM group. Age and duration of diabetes mellitus (DM) were found to have a significant link with CCT in children with T1DM. The duration of DM was also found to be significantly linked to the IOP. Gender and HbA1c levels were found to have no significant relationship with either CCT or IOP. 8 Conclusion Children with T1DM have significantly higher CCT and IOP than the average child. The duration of DM is a significant factor that impacts both CCT and IOP. In addition, age is another factor that affects CCT in children with T1DM.